The Influence of Social Media Marketing on Purchase Decisions Moderated by Electronic Word of Mouth at Cititex Kupang - Jessica Angelin; Yosefina K.I.D.D Dhae; Yonas F. Riwu; Rolland E. Fanggidae (Journal of Management and Business Innovation, 2026)
This study aims to analyze the influence of social media marketing on purchasing decisions with electronic word of mouth as a moderating variable at Cititex Kupang, a fashion retailer operating in Kupang City, Indonesia. The research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 100 respondents who met the criteria: consumers who had purchased or interacted with Cititex Kupang products through Instagram, were influenced by reviews or recommendations on Instagram, and had active social media accounts. Data analysis utilized simple linear regression and Moderated Regression Analysis (MRA). The results revealed that social media marketing significantly influences purchasing decisions at Cititex Kupang (t-count 9.733 > t-table 1.660; sig. 0.000 < 0.05). However, electronic word of mouth was not proven to moderate the relationship between social media marketing and purchasing decisions, as the interaction variable showed a significance value of 0.065 (> 0.05) with a negative coefficient direction, indicating a weakening tendency. This research contributes to the digital marketing literature by examining the moderating role of e-WOM in the relationship between social media marketing and purchase decisions, particularly in the context of local fashion retail in Eastern Indonesia, an area previously under-researched. The findings suggest that fashion retailers should optimize their social media marketing strategies through engaging content creation, active sharing, and community building. While e-WOM may not serve as a strong moderator, companies should still encourage customer reviews and testimonials to complement their promotional efforts. This study is limited to a single retail location (Cititex Kupang) with 100 respondents. Future research should expand the sample size, include multiple locations, and consider other variables such as price, product quality, and brand trust to provide a more comprehensive understanding of factors influencing purchase decisions.